The Influence of Education About "Isi Piringku" Using Healthy Plate Model Media on Increasing Nutritional Knowledge of Students at SMP Negeri 1 Deli Tua - Luthfia Chaerunnisa Sinaga; Lola Logaya Pane; Fitri Lamria Habeahan; Maria Ina Sintia; Sardima Sirait; Nada Amirah (Jurnal Kesmas Prima Indonesia, 2026)
This study aims to determine the effect of education about “Isi Piringku” using a healthy plate model media on increasing nutrition knowledge among students at SMP Negeri 1 Deli Tua. Nutrition plays a crucial role in supporting children's growth and development as well as maintaining health. The study employed a quasi-experimental design with a pretest-posttest approach involving 60 students. Data were collected through knowledge tests before and after education using the healthy plate model media. Kolmogorov-Smirnov normality test showed that the data were not normally distributed, therefore the non-parametric Wilcoxon Signed Rank Test was used for analysis. The results indicated that 59 out of 60 students showed an increase in nutrition knowledge scores after the intervention (p = 0.0001). This demonstrates that education using the "Isi Piringku" media model is effective in improving nutrition knowledge among SMP Negeri 1 Deli Tua students. It is recommended to utilize visual educational media to enhance nutrition understanding among students.